2017
DOI: 10.1002/2017gc006810
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic signatures of forearc basin formation mechanisms

Abstract: Tectonic deformation of accretionary wedges is often interpreted using stratigraphic patterns observed in forearc basins. However, similar stratigraphic patterns could evolve from different deformational processes making it difficult to uniquely reconcile stratigraphic patterns and the geodynamic history of natural accretionary wedges. Therefore, it is important to test the dynamic consistency of interpreted deformation histories. One approach is to compare synthetic stratigraphy of forearc basins generated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 67 publications
0
21
0
2
Order By: Relevance
“…Despite recent progress in numerical simulations (e.g., Fuller et al, 2006;Mannu et al, 2016Mannu et al, , 2017, it remains difficult to quantitatively evaluate how internal stratigraphic patterns in forearc basins form in response to changes in sediment influx/outflux over time due to the complex interactions between the overriding backstop, the subducting oceanic slab, the growing wedge, and the basin. It is thus necessary to focus on the forearc basin stratigraphy in terms of mass balance along the plate boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent progress in numerical simulations (e.g., Fuller et al, 2006;Mannu et al, 2016Mannu et al, , 2017, it remains difficult to quantitatively evaluate how internal stratigraphic patterns in forearc basins form in response to changes in sediment influx/outflux over time due to the complex interactions between the overriding backstop, the subducting oceanic slab, the growing wedge, and the basin. It is thus necessary to focus on the forearc basin stratigraphy in terms of mass balance along the plate boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not test the longitudinal sediment supply to the trench in this study, dominance of trench‐parallel turbidity currents has been reported from Sumatra (Moore et al, ), eastern Makran (Bourget et al, ), Nankai (Pickering et al, ), the southern Hikurangi margin (Lewis et al, ), the southern Lesser Antilles (Limonta et al, ), and the South Central Chile (Blumberg et al, ; Melnick & Echtler, ). For the case of the Nankai Trough, subduction of thickened trench fill sediment may cause out‐of‐sequence thrusting and uplift of the outer‐arc high (Mannu et al, ; Moore et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of a forearc basin at an accretionary margin is controlled by deformation of the accretionary wedge, which depends on various factors including the material properties of the wedge and the décollement (friction, cohesion, and pore fluid pressure), plate convergence (obliquity and velocity), isostatic response (uplift and subsidence), and external surface processes (erosion and sedimentation) (e.g., Byrne et al, ; Fuller et al, ; Graveleau & Dominguez, ; Gutscher et al, ; Malavieille et al, ; Mannu et al, ; Noda, , ; Simpson, ; Wang & Davis, ). Among these factors, external surface processes can strongly influence deformation of the accretionary wedge (e.g., Cruz et al, , ; Simpson, ; Storti & McClay, ) by (1) concentrating deformation at the rear of the wedge (Hardy et al, ; Storti & McClay, ), (2) reducing the taper angle (Bigi et al, ; Simpson, ; Storti & McClay, ), (3) decreasing the number of thrusts and widening the thrust spacing, which is likely caused by a reduction in differential stress in the wedge due to an increase in normal stress (Bigi et al, ; Fillon et al, ; Liu et al, ; Simpson, ; Zhang et al, ), (4) increasing the duration of folding at the upper ramp tip (Storti et al, ), (5) prolonging the phase of underthrusting and limiting the forward propagation of thrust activity (Del Castello et al, ; Hardy et al, ), (6) forming a trishear zone and causing limb rotation (Wu & McClay, ), (7) creating and reactivating out‐of‐sequence thrusts (Mannu et al, ; Storti et al, ), (8) stabilizing the rear of the wedge and increasing the rate of migration of the deformation front (Fillon et al, ), and (9) causing a switch from frontal accretion to synchronous thrusting and underthrusting due to local heterogeneity of the basal shear stress (Bigi et al, ; Del Castello et al, ; Storti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A2-A4 could be a reason for a lower angle of the wedge top slope α (Figures 10-12). In addition, downward force acting on the backstop increases a possibility to subside or rotate the backstop, and then to lead the décollement step-down, underplating of the subducting sediments, or tectonic erosion (Strasser et al, 2009;Kimura et al, 2011;Mannu et al, 2017).…”
Section: Retro-wedge Basinmentioning
confidence: 99%
“…The formation of a forearc basin at an accretionary margin is controlled by deformation of the accretionary wedge, which depends on various factors including the material properties of the wedge and the décollement (friction, cohesion, and pore fluid pressure), plate convergence (obliquity and velocity), isostatic response (uplift and subsidence), and external surface processes (erosion and sedimentation) (e.g., Byrne et al, 1988;Malavieille et al, 1993;Wang & Davis, 1996;Gutscher et al, 1998;Fuller et al, 2006;Graveleau & Dominguez, 2008;Simpson, 2010;Mannu et al, 2017;Noda, 2016Noda, , 2018. Among these factors, external surface processes can strongly influence deformation of the accretionary wedge (e.g., Storti & McClay, 1995;Simpson, 2010;Cruz et al, 2011) by (1) concentrating deformation at the rear of the wedge (Storti & McClay, 1995;Hardy et al, 1998), (2) reducing the taper angle (Storti & McClay, 1995;Bigi et al, 2010;Simpson, 2010), (3) decreasing the number of thrusts and widening the thrust spacing, which is likely caused by a reduction in differential stress in the wedge due to an increase in normal stress (Liu et al, 1992;Bigi et al, 2010;Simpson, 2010;Zhang et al, 2019), (4) increasing the duration of folding at the upper ramp tip (Storti et al, 1997), (5) prolonging the phase of underthrusting and limiting the forward propagation of thrust activity (Hardy et al, 1998;Del Castello et al, 2004), (6) forming a trishear zone and causing limb rotation (Wu & McClay, 2011), 7creating and reactivating out-of-sequence thrusts (Storti et al, 2000;Mannu et al, 2016), (8) stabilizing the rear of the wedge and increasing the rate of migration of the deformation front , and (9) causing a switch from frontal accretion to synchronous thrusting and underthrusting due to local heterogeneity of the basal shear stress …”
Section: Introductionmentioning
confidence: 99%